1976
DOI: 10.1021/bi00661a034
|View full text |Cite
|
Sign up to set email alerts
|

Conformational properties of dinucleoside monophosphates in solution: dipurines and dipyrimidines

Abstract: In order to obtain information about the conformational features in a polyribonucleotide at the nearest neighbor level, detailed nuclear magnetic resonance studies of the dinucleoside monophosphates ApA, ApG, GpA, UpU, CpC, UpC, and CpU were undertaken. Proton spectra were recorded at 100, 220, 270, or 300 MHz for D2O solutions, 0.01-0.03 M, pD 7.4 at 20+/-2 degrees C. Spectra of ApA, ApG, UpU, and UpC were also recorded in the temperature range of 70-90 degrees C. Unambiguous signal assignments of all proton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
120
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 185 publications
(149 citation statements)
references
References 67 publications
29
120
0
Order By: Relevance
“…5a and 5b show dimers; however, they also apply to n-mers where 5'-AMP molecules are added to both sides of the initial stack, leading to a perpetual headto-head or head-to-tail stacking pattern. Sarma and co-workers (54)(55)(56) have determined the molecular topology of 3',5'-, and 2',5'-pApAp dinucleotides in aqueous solution. In the first case the two adenine bases show a preference for a head-to-head stacking while the arrangement in the latter case is neither head-to-head nor head-to-tail.…”
Section: Resultsmentioning
confidence: 99%
“…5a and 5b show dimers; however, they also apply to n-mers where 5'-AMP molecules are added to both sides of the initial stack, leading to a perpetual headto-head or head-to-tail stacking pattern. Sarma and co-workers (54)(55)(56) have determined the molecular topology of 3',5'-, and 2',5'-pApAp dinucleotides in aqueous solution. In the first case the two adenine bases show a preference for a head-to-head stacking while the arrangement in the latter case is neither head-to-head nor head-to-tail.…”
Section: Resultsmentioning
confidence: 99%
“…Sugar pucker can influence the interphosphate distance between adjacent bases, with C′ 3 endo producing a more compressed backbone than C′2 endo (37). NMR studies have shown that the sugar pucker in poly(dT) is predominantly in the C′2 endo state (38) while poly(rU) is a 44∶56 mixture of C′2 endo and C′3 endo (39). Thus, we expect rU 40 to have a shorter contour length.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we expect rU 40 to have a shorter contour length. Also, while rU 40 is known to undergo the least stacking among the ribonucleotides, there is some evidence that rU 40 does in fact take part in some base stacking (39,40). We believe that base stacking in poly(rU) but not in poly(dT) may cause rU 40 to be more rigid than dT 40 .…”
Section: Discussionmentioning
confidence: 99%
“…monophosphates that are useful for chemical synthesis of short oligomers by diester chemistry or are used directly in enzymatic syntheses of various short oligomers [218][219][220][221] .…”
Section: Enzymatic Synthesis Of Deuterated Nucleosides or Nucleotidesmentioning
confidence: 99%